An outbreak of rubella at rural area of West Bengal, India in 2016 - Biswas, Dilip Kumar; Bhunia, Rama; Manna, Doli; Chattaraj, Anjan (South East Asia Journal of Public Health, 2017)
Rubella is a contagious, generally mild viral infection that occurs most often in children and young adults. The infection in pregnant women may cause foetal death or congenital defects known as congenital rubella syndrome (CRS). Globally, the incidence of CRS was from 0.4-4.3/1000 live birth. The aims of the study were to (i) investigate outbreak to determine the magnitude of outbreak, and (ii) analyze outbreak in term of time, place and person distribution, and recommend preventive measures. We conducted investigation by house to house active case search at Dumra village of Purba Medinipur district, West Bengal; India between February and May’ 2016. Epidemic curve was drawn to see the dynamic of outbreak and spot map was plotted to see the distribution of cases. Blood specimen was taken for serological test of virus. A total of 54 cases were identified; among those five cases were found positive for rubella (IgM). The attack rate (AR) among the women more 7.5% (27/358) than men 7.0% (27/388), with overall AR was 7.2% (54/746). Maximum cases were found among age group of 5-9 years with AR was 8.0% (23/286), followed by age group 0-4 years with AR was 3.9% (12/309). Median age was 8 years with rage from 0.6 to 33 years. Seventeen percent (9) cases were among female reproductive age (15-33 years). None of them were pregnant. Under five children were 33% (18/54) and 72% (13/18) were vaccinated with measles but none of them were vaccinated with rubella vaccine. All the patients were treated at home and at outpatient department. Outbreak of rubella was confirmed. We recommended introduction of rubella vaccine in National Immunization Schedule of India. South East Asia Journal of Public Health Vol.7(1) 2017: 17-22